Price Matching in Online Retail - Anna Bottasso; Simone Robbiano; Paolo Marocco (Global Labor Organization (GLO), 2023)
We analyze a sample of consumer-electronics products sold by the US NewEgg online-retailer to study the impact of Price Matching Guarantees (PMGs) policies on prices. By applying aDifference-in-Differences approach,we find that prices of the policy-adopting retailer increase by 4.7% during the policy validity period and up to five days after the treatment, while those of the major non-adopting competitor are not affected. Results are mainly driven by highlyrated, visible and expensive products, while the policy does not affect low-rated, less visible and cheaper ones. Overall findings are consistent with the hypothesis that PMGs act as price discrimination tools.
Keywords: L11; L13; L15; L81; 330; Price Matching Guarantees; Online Retailing; User Generated Contents; Difference-in-Differences; Price Discrimination; Collusion; Signalling